Assessing consumer empowerment and influencing factors in Central Bangka Regency: a multidimensional approach - Muhammad Faisal Akbar; Devi Valeriani; Panggio Restu Wilujeng; Mustofa Tohari (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
The rapid development of trade technology in Indonesia exposes consumers to potential exploitation during purchasing. This study examines consumer empowerment in Central Bangka Regency using primary data from 88 respondents across four districts. The Consumer Empowerment Index (CEI) value of 38.53, classified as